Brand Groundwork™ Analysis of the SatuSehat™ Digital Application - Dwi Anggia; Riska Yuliarosa; Verry Agusta (Jobmark: Journal of Branding and Marketing Communication, 2023)
As a new public health communication and service platform, the SatuSehat™ digital application requires adequate self-understanding and brand insight for subsequent branding development. This article analyzes SatuSehat™ brand insights as a brand of a public health service digital application provided by the Ministry of Health of the Republic of Indonesia using Wijaya’s Brand Groundwork Wheel (BGW) methodological and strategic approach. By focusing on six aspects of BGW: brand origin, brand dream, brand nature, brand soul, brand mate, and brand talent, as proposed by Wijaya (2010), the study found how SatuSehat™ has a dream to become a complete and integrated health service platform in Indonesia, integrating and synergizing patient data and information from all health facilities in Indonesia. With the character and spirit of speed, convenience, and practicality, SatuSehat™ continues the successful performance of its brand origin, PeduliLindungi™, a platform that has successfully become the government's mainstay in navigating, educating, and detecting the spread of the virus during the Covid-19 pandemic. With the competence, specialization, and essential talent as a public health servant, SatuSehat™ will continue to be the commander of public services, ensuring every Indonesian citizen can access easy, fast, practical, and integrated health information and services in real-time.